2013
DOI: 10.5551/jat.14340
|View full text |Cite
|
Sign up to set email alerts
|

Testing Endothelial Function and its Clinical Relevance

Abstract: Endothelial dysfunction as an integrating index of the risk factor burden and genetic susceptibility is an early marker of atherothrombotic disease. Therefore, tremendous interest exists in its measurement and determination of the clinical utility of the evaluation of endothelial function. Different invasive and non-invasive techniques exist for exploring various aspects of the pathobiology of the endothelium. As endothelial dysfunction is a diffuse-systemic disorder, the peripheral arteries, because of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 53 publications
3
110
1
1
Order By: Relevance
“…1 In this issue of the Journal, Sugihara et al reported for the first time that extremely low levels of SUA caused by SLC22A12/URAT1 loss-of-function mutations cause endothelial dysfunction in vivo, 12 as exhibited by flow-mediated dilation (FMD). 13 They initially found a positive correlation between SUA and FMD only in the hypouricemia group (SUA <2.5 mg/dl). Sequence analysis of genomic DNA revealed the clear differences in SUA levels between those groups.…”
Section: Editorial Effect Of Ua On Vascular Functionmentioning
confidence: 99%
“…1 In this issue of the Journal, Sugihara et al reported for the first time that extremely low levels of SUA caused by SLC22A12/URAT1 loss-of-function mutations cause endothelial dysfunction in vivo, 12 as exhibited by flow-mediated dilation (FMD). 13 They initially found a positive correlation between SUA and FMD only in the hypouricemia group (SUA <2.5 mg/dl). Sequence analysis of genomic DNA revealed the clear differences in SUA levels between those groups.…”
Section: Editorial Effect Of Ua On Vascular Functionmentioning
confidence: 99%
“…18 The determination of venous endothelial function is more complicated and invasive and is less reproducible than FMD. 19 Microinvasive techniques such as the dorsal hand vein dilation capability and radionuclide assessment of changes in the volume of legs provide limited information about venous endothelial function. [20][21][22][23] However, as ED is expected to be a systemic disorder affecting the whole circulatory system (arteries, veins, and microcirculation), determination of endothelial function of peripheral arteries may also provide insight into venous functional status.…”
Section: Determination Of Ed and Its Involvement In Vtementioning
confidence: 99%
“…13, 14 Thus, in this study, we evaluated endothelial function using FMD in patients with renal hypouricemia.…”
Section: Human Umbilical Endothelial Cells (Huvec) and Ua Transportermentioning
confidence: 99%